The Kingfisher visual factfinder : stars and planets, planet Earth, the living world, science and technology, world history, countries of the world - Kingfisher Books (Kingfisher Publications: London, 1993)
An encyclopaedic reference book that aims to present facts and figures in an enjoyable and stimulating way. It contains sections on countries of the world, Planet Earth, the living world, world history, science and technology, and the stars and planets.
Keywords: World history encyclopedias